PROTECTIVE EFFECTS OF N-ACETYLCYSTEINE AGAINST 5-FLUOROURACIL-INDUCED PULMONARY TOXICITY IN ALBINO RATS (Iraqi Journal of Medical Sciences, 2016)
Background:5-fluorouracil (5-FU) is a potent chemotherapeutic drug widely used in the treatment of cancer and acts by blocking DNA synthesis. N-acetylcysteine (NAC) is a pharmaceutical drug and nutritional supplement represents the rapidly absorbed form of the amino acid L-cysteine and acts as antioxidant.Objective:The current study aims to investigate the protective role of N-acetylcysteine administration against 5-FU induced pulmonary toxicity in albino rats.Methods: The study was conducted on 18 healthy adult female and male Wistar albino rats which were randomly selected and equally distributed into three groups of 6 rats for each. Group I served as a control group. Group II received 5-FU (20 mg in 2ml normal saline per kg body weight) by intraperitoneal injection for 7 consecutive days. Group III received intraperitoneal injections of N-acetylcysteine (200 mg/kg) 24 hour prior to each intraperitoneal injections of 5-FU for 7 consecutive days. The specimens of lung tissue of the three groups were extracted and prepared for light microscopic examination. The tissue sections were stained with Harris Hematoxylin and Eosin (H&E) stain and with Masson's trichrome stain.Results:Structural changes were observed in Group II (5-FU recipient group compared to Group I (control group)including emphysematous dilatation of the alveoli, proliferation of BALT (bronchus associated lymphatic tissue), thickening of alveolar walls with mononuclear inflammatory cells infiltration, in addition to congestion and hemorrhage of pulmonary interstitium. Pretreatment with N-acetylcysteine effectively reduces the changes induced by 5-FUon the lung and reverts the abnormal pulmonary structure to become nearer to the norms.Conclusion:Treatment with N-acetylcysteine prior to 5-fluorouracil effectively attenuated 5-FU induced pulmonary damage and reverted the abnormal structural changes to near normal. Thus NAC has a protective potential in ameliorating 5-fluorouracil induced pulmonary toxicity.Key words:5-Fluorouracil, N-acetylcysteine, rats, lung, emphysema.
Keywords: 5Fluorouracil; Nacetylcysteine; rats; lung; emphysema